Penerapan Goal Questions Metrics Terhadap Aplikasi Monitoring Sales Consultant - Andreas Dwi Setiawan; Natalinda Pamungkas; Widyatmoko Widyatmoko (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
Monitoring is a process of monitoring and analyzing information based on certain indicators. Every company engaged in distribution and promotion must carry out monitoring activities. Including PT. Single Paint Factory, Djaja Indah, Kediri Branch, which also continuously monitors the sales results of the sales consultants who work in several partner stores. The process of reporting sales results that have been carried out so far is still using conventional methods so that sometimes it interferes with the monitoring process due to delays in sending reports. To make this easier, the author makes a website-based monitoring application to help smooth the monitoring process of Sales Consultant sales results. To produce a quality application, the author uses the goal question metrics method as a method for measuring application quality. Goal Question Metric (GQM) is a method used to define application measurement models. The application of the GQM method in this study was carried out with the initial stage of factor analysis of the application quality model based on the ISO 25010 Quality Model. The next stage was making questionnaire questions regarding application characteristics and calculating the results of the questionnaire with the weighted summattion metric. From the results of measuring the quality of this monitoring application, the average quality value is 3.08, which means that this monitoring application is included in the application with good quality (Medium). The functionality available in the monitoring application is in accordance with the needs of users of the sales consultant monitoring application.